Human-animal agency in reindeer management: Sami herders perspectives on vegetation dynamics under climate change - Horstkotte, Tim; Utsi, Tove Aagnes; Larsson-Blind, Åsa; Burgess, Peter; Johansen, Bernt; Kayhko, Jukka; Oksanen, Lauri Kalervo; Forbes, B.C. (Ecosphere, 2017)
Source at http://dx.doi.org/10.1002/ecs2.1931 Many primary livelihoods in Arctic and sub-Arctic regions experience accelerating effects of environmental change. The often close connection between indigenous peoples and their respective territories allows them to make detailed observations of how these changes transform the landscapes where they practice their daily activities. Here, we report Sámi reindeer herders’ observations based on their long-term inhabitance and use of contrasting pastoral landscapes in northern Fennoscandia. In particular, we focus on the capacity for various herd management regimes to prevent a potential transformation of open tundra vegetation to shrubland or woodland. Sámi herders did not confirm a substantial, rapid, or large-scale transformation of treeless tundra areas into shrub- and/or woodlands. However, where they observe encroachment of open tundra landscapes, a range of factors was deemed responsible. These included abiotic conditions, anthropogenic influences, and the direct and indirect effects of reindeer. The advance of the mountain birch tree line was in some cases associated with reduced or discontinued grazing and firewood cutting, depending on the seasonal significance of these particular areas. Where the tree line has risen in elevation and/or latitude, herding practices have by necessity adapted to these changes. Exploiting the capacity of reindeer impacts on vegetation as a conservation tool offers time-tested adaptive strategies of ecosystem management to counteract a potential encroachment of the tundra by woody plants. However, novel solutions in environmental governance involve difficult trade-offs for ecologically sustainable, economically viable, and socially desirable management strategies.